KUALITAS BIJI SORGUM MANIS VARIETAS NUMBU DENGAN PEMBERIAN PUPUK SUMBER FOSFAT YANG BERBEDA - Winata, N.A.S.H.1; D.R. Lukiwati; E.D. Purbajanti Purbajanti (Agrovigor, 2014)
Sorghum is a source of animal feed poultry and ruminants . Source of phosphate fertilizer consists of SP36 ( water soluble ) and rock phosphate ( BP ) ( acid soluble ) . Manure comes from the decomposition of faeces , urine and the rest of the animal feed . Charcoal is used as a soil amendment , because of its improved physical properties soil . The study was conducted from March to August 2013 in the collection of cropland Faculty of Animal Husbandry and Agriculture Diponegoro University . The experimental design used in this study is a randomized block design ( RBD) with three replications as a group . Study treatment consisted of T0 = Control , T1 = SP 36 , T2 = Rock Phosphate , T3 = Manure , T4 = Manure " Plus " , T5 = Charcoal , T6 = Rock Phosphate + Charcoal , T7 = SP 36 + Charcoal , T8= Charcoal +Manure , T9 = Manure " Plus " + Charcoal . Manure " plus " can be used as a substitute for SP36 . Pile " plus " produce the same levels of P with SP36 . Pile " plus " gives the results of the different levels of P seed .Keyword: Sorghum bicolor  (L.) Moench, seeds quality, manure, SP36, rock phosphate.